2018
DOI: 10.1177/0897190018798881
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adjusted Versus Unadjusted Doses of Polymyxin B Based on Renal Function and Incidence of Acute Kidney Injury

Abstract: The results from this study support the use of polymyxin B without any dose adjustment in the setting of renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…These results caused some confusion, so we reanalyzed the data and found that there was no statistically significant difference in the incidence of neurotoxicity (p = 0.386) and mortality (p = 0.206) between the two groups. The following research by Peyko et al (Peyko and Cohen, 2020) also supported this conclusion. They found that there was no difference between the two groups in the incidence of acute kidney injury at day 7, occurrence of microbiological cure, clinical cure, and 30-days mortality (Table 1, Entry 9).…”
Section: What Are Recent Recommendations In the Latest Research?mentioning
confidence: 57%
“…These results caused some confusion, so we reanalyzed the data and found that there was no statistically significant difference in the incidence of neurotoxicity (p = 0.386) and mortality (p = 0.206) between the two groups. The following research by Peyko et al (Peyko and Cohen, 2020) also supported this conclusion. They found that there was no difference between the two groups in the incidence of acute kidney injury at day 7, occurrence of microbiological cure, clinical cure, and 30-days mortality (Table 1, Entry 9).…”
Section: What Are Recent Recommendations In the Latest Research?mentioning
confidence: 57%
“…This process may explain how polymyxin B causes damage to the kidney when it is cleared as a nonrenal drug. Previous studies reported that the incidence of polymyxin B-induced nephrotoxicity ranged from 18.2% to 46.1% [18,19]. However, different definitions of nephrotoxicity were applied, and a broad polymyxin B dose was administered, which may explain the different results in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…The survival was no difference in 28-day mortality in patients that received 100, 150, 200 mg/day PMB. Some studies found that there was no difference in PMB daily dose between survivors and nonsurvivors [ 20 , 30 ]. But other studies suggested that the daily dose of PMB treatment failure in CR-GNB infections among critically ill patients was lower than success [ 9 ].…”
Section: Discussionmentioning
confidence: 99%